(untitled) (Journal of Educational Sciences, 2016)
In this article there are considered the problems and peculiarities of forming of pedagogical for competence of the teacher of physical culture. The authors conducted the сопаставительный analysis of the terms «competence», «qualifi cation», «pedagogical competence», the peculiarities of each category in the preparation of teachers of physical training. The article presents the results of experimental work conducted in the Kazakh Academy of sport and tourism, in the school-gymnasium №122 g. Almaty, Kazakhstan- Russian gymnasium. I.V. Panfi lova str. Almaty, in secondary school №20 of the Merke district of Zhambyl oblast.